Analysis of Mild Traumatic Brain Injury Outpatient Follow-Up. Issue 4 (July 2020) - West, Sarah K.; Fletcher, Brian; Rollins, Allison; Will, Jennifer; Rozzell, Monica; Burton, Josh; Spalding, M. Chance
Abstract : Background: Mild traumatic brain injury (mTBI) remains a prevalent public health concern. Implementation of an mTBI guideline encouraged screening all patients at risk for mTBI, followed by outpatient follow-up in a "concussion clinic." This resulted in an increase in inpatient concussion evaluations, followed by high-volume referral to the concussion clinic. This prompted the routine use of an outpatient mTBI symptom screening tool. The purpose of this quality improvement study was to analyze the characteristics of an mTBI population at outpatient follow-up and describe the clinicians' care recommendations as determined through the use of an mTBI symptom screening tool. Methods: This is a retrospective review of mTBI patients at a Level 1 trauma center. The study includes patients who completed a concussion screening in the outpatient setting over a 6-month period. Patients were included if older than 16 years, sustained blunt trauma, and had a formal neurocognitive evaluation by a certified speech therapist within 48 hr of initial injury. Results: Of the 247 patients included, 197 (79.8%) were referred to the concussion clinic, 33 (13.4%) had no further outpatient needs, and 17 (6.9%) were referred for outpatient neurocognitive rehabilitation. On follow-up, 97 patients were deemed to have no further postconcussion needs by the trauma nurse practitioner; 57 patients were cleared by the speech therapist. In total, 43 outpatient mTBI follow-up encounters resulted in referral for ongoing therapy. Conclusion: Routine screening for concussion symptoms and detailed clinical evaluation allows for prompt recognition of further posttraumatic mTBI needs.